Hume’s Guillotine and Legal Positivism - Baltrimienė, Milda (Problemos, 2018)
[only abstract in English; full article and abstract in Lithuanian] This article analyses the impact of Hume’s guillotine – thesis that there is a distinction between “is and “ought” statements – to the philosophy of legal positivism. Theories of legal positivism emphasize that law is a social phenomenon and that it could be defined and fully explained only by referring to social facts. Accordingly, the analysis of law should limit itself only to descriptive statements. Otherwise, the usage of normative reasoning leads to the conceptual mistakes. In other words, from claims which laws are the most appropriate ones, it cannot be deduced that these laws should be valid. Therefore, the acceptance of Hume’s guillotine was one of the crucial factors during the development of the main premises of legal positivism. In this article it is aimed to prove that legal positivism encounters theoretical contradictions while seeking to explain the normativity of law, which in that Hume’s guillotine can be applied to legal positivism itself.